Utilization of multimedia-assisted teaching materials in educational statistics courses on students' mathematical connection ability - Wahyuni, Putri; Yolanda, Fitriana; Candra, Oki; Putri, Dini Palupi; Rahmawarni, Desi (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to examine the effectiveness of multimedia-assisted teaching materials in improving students’ mathematical connection skills in an Educational Statistics course. It also explores the conditions under which multimedia-based instruction may or may not outperform conventional teaching methods. Method: A quasi-experimental pretest–posttest control group design was employed. The sample consisted of an experimental group (n = 30) that utilized multimedia-assisted teaching materials and a control group (n = 30) that received conventional instruction. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, paired-sample t-tests, independent-sample t-tests, and effect size analysis (N-Gain and Cohen’s d). Findings: Both groups demonstrated significant improvement. However, the experimental group showed a substantially greater increase (mean difference = 11.80) compared to the control group (mean difference = 7.24). The independent-sample t-test indicated a statistically significant difference between the two groups (t (58) = -2.25, p = 0.028), favoring the experimental group. Effect size analysis revealed a Cohen’s d of 0.58 (medium effect) and an N-Gain of 0.35 (medium category) for the experimental group, while the control group showed an N-Gain of 0.19 (low category). Significance: These findings suggest that multimedia-assisted learning is not inherently superior; its effectiveness depends on factors such as instructional design quality, cognitive load management, implementation fidelity, and students’ readiness. This study contributes to the literature by offering a more critical perspective on the conditional effectiveness of multimedia in mathematics education and highlights the importance of context-sensitive technology integration.